Teacher Competence in the Implementation of the Malaysian Skills Certificate in Special Education Integration Programs - RAFEI, SITI RAFIDA RAIHAN; MOHAMAD, MIMI MOHAFFYZA; MAFARJA, NOFOUZ (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study evaluates the competence of Special Education Integration Program (SEIP) teachers in implementing the Malaysian Skills Certificate (MSC), focusing on skills, knowledge, and attitudes. Utilizing a quantitative approach, data were collected from 66 SEIP teachers across six secondary schools via a questionnaire. Descriptive statistics and one-way ANOVA were used for analysis. Results revealed that SEIP teachers demonstrated moderate levels of competence in skills and knowledge but high competence in attitude. Teachers with skill certification qualifications showed significantly higher skills and knowledge than those without such qualifications. However, no significant differences were observed in attitudes based on skill qualification levels. SEIP teachers exhibited a positive attitude towards implementing the MSC and fostering an inclusive learning environment. Additionally, significant differences emerged in training needs and skill levels (F (4,61) (5.51) as well as knowledge levels (F (4,61) (4.48), across different skill qualification levels. Conversely, attitudes and skill qualification levels were not significantly correlated (F (4,61) (2.11). The findings highlight the importance of continuous professional development to enhance SEIP teachers’ skills and knowledge for effective MSC implementation. These insights are instrumental in designing future training programs tailored to their needs.